Analisis Faktor Pemlihan Alat Kontrasepsi IUD Pasca Persalinan DI Wilayah Puskesmas Rawalo - Septiana Tunjung Sari; Purwati (NERSMID : Jurnal Keperawatan dan Kebidanan, 2023)
The high population growth in developing countries and the high birth rate in Indonesia are currently important problems that require extra attention in their management to achieve birth control. According to the Head of BKKN Hasto, there is Postpartum Family Planning Data in 2022 which is still very low at 15.8% so that there are still 85% of mothers who have not used Postpartum Family Planning. Success Rate Postpartum IUD is a contraceptive method that is safe to use for almost all women with an effectiveness rate of 99.94%, Postpartum IUD installation is done immediately after giving birth in less than 48 hours. Based on this, this study aims to explore the use of postpartum IUD contraception in the Rawalo Health Center area. A comparative study was carried out using documentation of delivery registers at the Rawalo Health Center for 8 postnatal IUD acceptors in the Rawalo Health Center area using a purposive sampling technique with a phenomenological approach.The results showed that the characteristics of the primary informants were 8 acceptors aged 20-35 (75%), while those aged > 35 years (25%). The informants of this research are acceptors. This research was conducted in-depth interviews and observations. The results of this study prove that the factor analysis for choosing a postpartum IUD contraceptive device in the Rawalo Health Center area is the reason acceptors choose a postpartum IUD contraceptive device, husband/family support after using a postpartum IUD, KIE that is not carried out optimally and access to health services that have been quite good and for a fairly close distance of about 10 minutes.